An Investigation of Power Effect on Conspicuous and Non-Conspicuous Consumption of Counterfeited Branded Products - Haque, Sadia (2011)
Two experiments have been conducted in this research work to examine two contradictory predictions based on two opposing body of literature on power and its psychological effect on consumer behaviour. Specifically the present work investigated how experiencing high versus low power help to produce unique consumption patterns in the context of counterfeited luxury branded products. In experiment 1, based on accumulating evidence that (a) powerlessness is an aversive state, (b) status is one source of power, (c) products can signal status which is applicable for counterfeited products as well, and (d) powerlessness drives people to take more risk to compensate their disadvantaged situation, the researcher has predicted that low power will lead consumers to have a more positive attitude and purchase intention for counterfeited luxury branded products compared to that of consumers in high power in terms of conspicuous consumption. At the same time, the researcher has also predicted that high power will lead consumers to have a more positive attitude and purchase intention for counterfeited luxury branded products compared to that of consumers in low power in terms of non-conspicuous consumption. The result from the experiment 1 has shown an opposing result to the prediction exhibiting that high power leads consumers to have more positive attitude and purchase intention for counterfeited luxury branded products in terms of conspicuous consumption compared to that of low power. The result has also shown that low power leads consumers to have more positive attitude and purchase intention for counterfeited luxury branded products in terms of non-conspicuous consumption compared to that of high power. On the other hand, according to a competing body of literature where behavioural approach and inhibition theory plays, holding power leads people to take more risk but powerlessness leads people to avoid risk. Based on that evidences, in experiment 2, the researcher of this present study predicted that high power will lead consumers to have more positive purchase consideration and purchase intention for counterfeited luxury branded products in terms of conspicuous consumption compared to that of low power. At that same time, the researcher also predicted that low power will lead consumers to have more positive purchase consideration and purchase intention for counterfeited luxury branded products in terms of non-conspicuous consumption compared to that high power. The result from the experiment 2 has supported the prediction showing that high power leads consumers to have more positive purchase consideration and purchase intention for counterfeited luxury branded products in terms of conspicuous consumption compared to that of low power. The result has also shown that low power leads consumers to have more positive purchase consideration and purchase intention for counterfeited luxury branded products in terms of non-conspicuous consumption compared to that of high power. This research findings not only has a potentially noticeable significance in the contradictory existing knowledge on power but also considering the fluctuation of power position in peoples’ everyday life and the yet much to be discovered about the psychology of consumers who are lean to buy counterfeited luxury branded products, this research outcome has also a potential to contribute in these fields of academic and business concerns.